2020
DOI: 10.1177/1046878120931602
|View full text |Cite
|
Sign up to set email alerts
|

Gaming in the Time of COVID-19

Abstract: Reflecting on Gaming in the Time of Pandemic Crisis As the COVID-19 pandemic affects us all, I focus here, in this editorial, on some aspects related to gaming and simulation in these challenging times. There have been some reflective conversations within the ISAGA network that I would like to share with you. My honored colleague, Simulation & Gaming advisory board member, Jan Klabbers started a discussion via email some weeks ago by stating: "Reflecting on all the confusing and threatening news, on the rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 12 publications
0
21
0
2
Order By: Relevance
“…Holistically, AR games such as Pokémon GO and Harry Potter: Wizards Unite provide virtual socialization with other people, motivate players to sustain exercise, and offer a daily routine during the lockdown, therefore establishing mental coping strategies to benefit well-being during COVID-19 lockdown. As stated recently in a commentary on gaming in the time of COVID-19, Kriz [ 67 ] suggested that “games have the potential to entertain and relax, to lower stress (maybe even provide an escape for a while from the real problems and fear accompanying the pandemic) and to provide the opportunity to interact with friends through (virtual) forms of play.”…”
Section: Discussionmentioning
confidence: 99%
“…Holistically, AR games such as Pokémon GO and Harry Potter: Wizards Unite provide virtual socialization with other people, motivate players to sustain exercise, and offer a daily routine during the lockdown, therefore establishing mental coping strategies to benefit well-being during COVID-19 lockdown. As stated recently in a commentary on gaming in the time of COVID-19, Kriz [ 67 ] suggested that “games have the potential to entertain and relax, to lower stress (maybe even provide an escape for a while from the real problems and fear accompanying the pandemic) and to provide the opportunity to interact with friends through (virtual) forms of play.”…”
Section: Discussionmentioning
confidence: 99%
“…Second, video games provide a powerful medium for understanding complex situations, such as the pandemic itself or the fake news associated with it. 51 For example, Factitious (http:// factitious.augamestudio.com/) is a simple game that asks players to read a small article and then decide if it is real or fake news. 52 Factitious tries to help players think more critically about fake news by providing contents that make users think critically about the content and the source.…”
Section: Social Technologies: Using Technology To Promote Social Intementioning
confidence: 99%
“…Programming includes trivia nights, virtual escape rooms, and game nights using board game platforms/simulators and other software, such as Jackbox Games (2021). Attendance to these events has lessened compared to inperson programming; however, students who attend enjoy and appreciate the virtual programming (Costello, 2021), which has become a unique tool in combatting the stresses of social isolation (Kriz, 2020).…”
Section: Virtual Board Game Programsmentioning
confidence: 99%